Habits of Five Brazilian Snakes with Coral-snake Pattern, Including a Summary of Defensive Tactics - Sazima, Ivan (1991)
Habitat, activity period, food, predators, and defensive behavior are briefly described for five species of snakes with coral-snake pattern, sympatric in southeastern Brazil: Micrurus frontalis, M. lemniscatus, Erythrolamprus aesculapii, Oxyrhopus guibei, and Simophis rhinostoma. Defensive behaviors were analyzed by numerical methods in order to evaluate the degree of similarity between these species. The similarity between defensive displays is supposed to be due either to phylogenetic affinity or to mimetic convergence. © 1991, Taylor & Francis Group, LLC. All rights reserved.